Decoding travellers’ willingness to pay more for green travel products: closing the intention–behaviour gap - Agag, Gomaa; Brown, Abraham; Hassanein, Ahmed; Shaalan, Ahmed (Taylor & Francis, 2020)
In the complex context of green consumption, researchers have examined the impact of many variables on pro-environmental behaviours, but have paid little attention to the effects of specific combinations of factors. This study fills this gap, using innovative methods to show how a combination of demographic variables, values, normative influence, personality traits and beliefs can stimulate travellers’ willingness to pay more (WLP), using one qualitative and two quantitative studies. In a strong methodological contribution, we develop a model based on complexity theory, which was validated using fuzzy-set qualitative comparative analysis (fsQCA) of 642 travellers. The results indicate that our integrated model has a favourable level of predictive power for travellers’ behaviour. Our findings suggest that no single factor is sufficient to drive travellers’ willingness to pay more, but the results of the fsQCA in four configurations propose eight causal recipes for achieving high WLP. Alongside its significant methodological contribution, our study makes strong theoretical and practical contributions, including how managers can target their green travel products more effectively.
Keywords: theory of planned behaviour; configurational modelling; complexity theory; fsQCA